The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-92171-6
|View full text |Cite
|
Sign up to set email alerts
|

Nano-metals forming bacteria in Egypt. I. Synthesis, characterization and effect on some phytopathogenic bacteria in vitro

Abstract: Bacterial metal reducers were isolated from water samples collected from harsh condition locations in Egypt. Four selected isolates were identified as Enterococcus thailandicus, Pseudomonas putida, Marinobacter hydrocarbonoclasticus, and P. geniculata for Copper (Cu), Iron (Fe), Cobalt (Co) and Zinc (Zn) Nanoparticles (NPs) production sequentially. Nitrate reductase enzyme was assayed for bacterial isolates which demonstrated that P. putida, and M. hydrocarbonoclasticus have the maximum enzyme production. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…Depending on the results obtained from our findings in the previous study [ 38 ], it proved the ability of FeNPs to act as antibacterial agents of D. solani . Thus FeNPs were chosen in this study to test the uptake in plant tissue.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Depending on the results obtained from our findings in the previous study [ 38 ], it proved the ability of FeNPs to act as antibacterial agents of D. solani . Thus FeNPs were chosen in this study to test the uptake in plant tissue.…”
Section: Discussionsupporting
confidence: 64%
“…Nano-metals forming bacteria E. thailandicus, P. putida, M. hydrocarbonoclasticus , and P. geniculata for Copper (Cu), Iron (Fe), Cobalt (Co), and Zinc (Zn) nanoparticles (NPs) production sequentially as reported in our previous study Part I [ 38 ], were tested for advanced studies on soft rot ( Pectobacterium carotovorum subsp. carotovorum and Enterobacter cloacae ) and blackleg ( Dickeya solani ) genera, as follow:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy-Dispersive X-ray spectroscopy (EDX):EDX analysis gives qualitative as well as quantitative status of elements that may be involved in the formation of NPs and proves the ability of bacterial cells to reduce and accumulate metalsfrom the culture medium [17] . In our study reveals that Energy dispersive Xray spectroscopic profile of AgNPs was confirmed by optical absorption peak at 3 keV, which is typical for silver nanocrystallite absorption.…”
Section: Scanning Electron Microscopy (Sem) With Energy Dispersive X-...mentioning
confidence: 99%
“…First, low-cost commercial ZnO NPs serve as the active core of nanocomposite against Psa. [50][51][52][53][54] In addition, the incorporation of PDA ensures uniform deposition of the metal enzyme-like active sites on the surface, enhancing biocompatibility. 55 The nanocomposites, with excellent CAT-like activity, exhibit K m and V max values superior to that of most reported nanozymes, efficiently converting H 2 O 2 into O 2 .…”
Section: Introductionmentioning
confidence: 99%